Distribution And Density Functions Of Continuous Random Variables, Their Properties - Yodgarov Samad Zhurayevich; Yuldosheva Aliya Qodirjon qizi (Genius Journals, 2024)
This article provides information about the distribution and density functions of continuous random variables and their properties. The article also presents results that directly follow from the properties of distribution and density functions. In addition, the article also describes in detail how to find the mathematical expectation using the distribution and density functions of continuous random variables.
Keywords: probability of an event; function; interval; density function